Sosialisasi dan Pelatihan Guna Meningkatkan Motivasi Belajar dan Minat Berwirausaha di Lingkungan Pelajar Pada Panti Asuhan Ar-Rahman Medan - Siregar, Alyad Ul; Lubis, Desy Irana Dewi; Isnaini Nur Azhara; Khayru Aqillah; Mhd Rahmad Ramadhan; Pardosi, Wanda (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2023)
Community service is the process of implementing knowledge learned in tertiary institutions in order to provide the widest possible benefit to society. One form of service activity is this activity, which aims to foster students' interest in entrepreneurship, which can provide benefits to the community, especially in the environment. Community service activities were carried out at the Ar-Rahman Orphanage in Medan. A series of activities in the form of providing learning motivation, training in entrepreneurship, and providing education in the process of making